Chromosome-level reference genome of Tylorrhynchus heterochaetus (Annelida, Nereididae) - Yang, Wei; Zhang, Xuemin; Fan, Bin; Si, Yuanyuan; Xu, Ruiwen; Li, Shengkang; Meng, Zining; Chen, Xinghan (Frontiers in Genetics, 2026)
The Tylorrhynchus heterochaetus, a polychaete benthic invertebrate belonging to the Nereididae family, has emerged as a promising aquaculture species. It is highly regarded for its nutritional profile, with protein accounting for up to 60% of its dry weight, as well as its balanced amino acid composition. This has earned it the nickname “aquatic cordyceps”. However, wild populations of this species have declined significantly due to environmental shifts and human activities, with local extinctions reported in certain regions. A critical barrier to advancing its population genetics and conservation biology has been the absence of a chromosomal-level reference genome for T. heterochaetus. To address this gap, we present the first chromosome-level genome assembly of T. heterochaetus, generated using PacBio HiFi sequencing data and Hi-C technology. The final assembly spans 782.25 Mb with a scaffold N50 of 75.39 Mb, successfully anchored to 11 pseudo-chromosomes. Repetitive sequences account for 428.09 Mb (54.73%) of the genome, and 20,145 protein-coding genes were annotated. This study provides foundational insights into the genetics, genomics, and evolutionary history of T. heterochaetus, laying a critical groundwork for future research and enabling the development of targeted genetic conservation strategies.